2022
DOI: 10.1111/1752-1688.13077
|View full text |Cite
|
Sign up to set email alerts
|

Reduced complexity models for regional aquatic habitat suitability assessment

Abstract: Generalizable methods that identify suitable aquatic habitat across large river basins and regions are needed to inform resource management. Habitat suitability models intersect environmental variables to predict species occurrence, but are often data intensive and thus are typically developed at small spatial scales. This study estimated mean monthly aquatic habitat suitability throughout Utah (USA) for Bonneville Cutthroat Trout (Oncorhynchus clarkii utah) and Bluehead Sucker (Catostomus discobolus) with pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 184 publications
0
2
0
Order By: Relevance
“…With respect to digital elevation models, for example, the highest available resolutions are not always optimal for ecosystem modeling or terrain representation (e.g., [ 46 , 47 , 48 ]). Several studies have also found that, in addition to advantages in computational efficiencies and implementation costs, reduced-complexity models provide more accurate and useful results in many environmental modeling contexts (e.g., [ 9 , 10 , 11 , 12 , 49 , 50 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to digital elevation models, for example, the highest available resolutions are not always optimal for ecosystem modeling or terrain representation (e.g., [ 46 , 47 , 48 ]). Several studies have also found that, in addition to advantages in computational efficiencies and implementation costs, reduced-complexity models provide more accurate and useful results in many environmental modeling contexts (e.g., [ 9 , 10 , 11 , 12 , 49 , 50 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of complexities of evolutionary sequences parallels the rise of reduced-complexity models in ecology, hydrology, and geomorphology. Including more factors, processes, or constraints in a model tends to reduce the generality of the results, and simpler models often produce satisfactory or even more accurate results (e.g., [ 9 , 10 , 11 , 12 ]). However, the appropriate level of complexity (in terms of the number of variables, parameters, and processes included in the model) for the problem at hand is not always clear [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%